Role of Hyperglycemia in the Senescence of Mesenchymal Stem Cells - Yin, Min; Zhang, Yan; Yu, Haibo; Li, Xia (Frontiers in Cell and Developmental Biology, 2021)
The regenerative and immunomodulatory properties of mesenchymal stem cells (MSCs) have laid a sound foundation for their clinical application in various diseases. However, the clinical efficiency of MSC treatments varies depending on certain cell characteristics. Among these, the roles of cell aging or senescence cannot be excluded. Despite their stemness, evidence of senescence in MSCs has recently gained attention. Many factors may contribute to the senescence of MSCs, including MSC origin (biological niche), donor conditions (age, obesity, diseases, or unknown factors), and culture conditions in vitro. With the rapidly increasing prevalence of diabetes mellitus (DM) and gestational diabetes mellitus (GDM), the effects of hyperglycemia on the senescence of MSCs should be evaluated to improve the application of autologous MSCs. This review aims to present the available data on the senescence of MSCs, its relationship with hyperglycemia, and the strategies to suppress the senescence of MSCs in a hyperglycemic environment.